Multidimensional examination of the performances of a liner shipping network: Trunk line/route operated by conventional (Panamax Max) and mega (ULC - ultra large container) ships - Milan Janić (Journal of Shipping and Trade (JST), 2018)
This paper deals multidimensional examination of performances of a trunk line/route of liner container-shipping network serving an intercontinental supply chain by the conventional (Panamax Max) and mega (ULC - Ultra Large Container) ships. The trunk line/route of the network includes the supplier and the customer seaport of freight shipments consolidated into containers (TEU (Twenty Foot Equivalent Unit)), and the container ships operated by liner shipping carriers and/or their alliances providing transport services between them. The supplier and the customer seaport can be either the main seaports of the line or the hubs of the H&S (Hub-and-Spoke) network of particular liner container-shipping carriers. The multidimensional examination implies defining and developing the analytical models of indicators of the trunk line's infrastructural, technical/technological, operational, economic, environmental, and social performances and their application to the selected real-life case. The infrastructural performances relate to the characteristics of infrastructure (berths) and container terminals in the seaports at both ends of the line. The technical/technological performances reflect the characteristics of facilities and equipment for loading/unloading and storing TEU shipments in these terminals, and that of the container ships transporting them. The operational performances include the transport service frequency, size, transport work and technical productivity of the deployed container ship fleet while serving a given volume of TEU flows during the specified time. The economic performances contain the inventory, handling, transport, and external costs of handling the TEU flows. The environmental performances relate to the fuel consumption and consequent emissions of GHG (Green House Gases). Finally, the social performances in terms of impacts generally refer to noise, congestion, and safety. The models of indicators of performances have been applied to the liner container-shipping trunk line/route connecting the East Asia and North Europe operated exclusively by two above-mentioned categories of ships according to the "what-if" scenario approach. The results have indicated the very high sensitivity of all considered indicators of performances to the category of deployed ships under given conditions. As well, they have shown to be dependent on each other - the operational on the technical/technological, and the economic, environmental, and social on the technical/technological and operational.
Keywords: 650; Liner container-shipping networks; Trunk line/route; Performances; Indicators; Analytical models; Conventional and mega container ships